AUTOMATIZACIÓN DE EXPERIMENTOS CON ARDUINO. - LESTEIRO-TEJEDA, J. A.; HERNÁNDEZ-DELFÍN, D.; BATISTA-LEYVA, A. J. (Revista Cubana de Física)
Experimentation is an essential component of the Scientific Method. Performing precise and exact experiments creates knowledge about the Universe, key for the formulation of new theories and for testing them, once they are formulated. Trending in modern experimental physics is the design of automatized measurement installations, which guaranties the constancy of experimental conditions, as well as an extreme flexibility in the measurement's design. Keeping low the cost of the equipment is something very important. University curricula on experimental physics must be adapted to these requirements if we want to graduate professionals well fitted to modern science and industry. In the present contribution we first discuss the experimental objectives in the curricula of the students at InSTEC, University of Havana. Then we analyze the use of Arduino based devices in the automation of some laboratory experiments and finally discuss the potential benefits for the professional performance and professional competences after graduation.